2014
DOI: 10.2478/bpasts-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on synthetic data-based calibration models for low resolution open-path FTIR spectroscopy

Abstract: Abstract. This article presents the problem of determining the gas concentration under conditions of changing temperatures. The solution to this problem is based on spectral measurements using chemometric models. Such problems arise when measuring gases during various industrial processes, mainly the pyrolysis process. Chemometric models are built using synthetic calibration data. Line-by-line and statistical models were applied for spectra modelling. The effect of temperature on extracting the gas concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Recently, the influence of temperature on the accuracy of the gas determination was performed. In many papers [17][18][19] it was shown that even a few degrees of temperature difference can result in noticeable and significant errors. Therefore, various methods of temperature correction are created.…”
Section: Temperature Problem In Spectrometric Measurementmentioning
confidence: 98%
“…Recently, the influence of temperature on the accuracy of the gas determination was performed. In many papers [17][18][19] it was shown that even a few degrees of temperature difference can result in noticeable and significant errors. Therefore, various methods of temperature correction are created.…”
Section: Temperature Problem In Spectrometric Measurementmentioning
confidence: 98%
“…As a scattering phase function of the tissue, use was made of the Henyey -Greenstein function with the parameter g(λ). Modeling and approximation of spectral features is a commonly applied approach of data analysis in different kind of spectroscopic methods [9][10].…”
Section: Analytical Calculation Of Diffuse Reflectance Characteristicmentioning
confidence: 99%
“…Using Gaussian shape is natural in measuring spectra from illuminated FBGs [12] [13]. Techniques of fitting measured or simulated spectra are developing in some spectroscopy analysis [14] [15]. Relatively new method of detecting peak is using the neural networks [11] [16].…”
Section: Introductionmentioning
confidence: 99%